Intracranial germinoma – a case report - Subha, Sethu Thakachy; Puraviappan, Periyannan; Narenthiranathan, N. Ramesh; Banarsi Dass, Dipak (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Intracranial germinomas belong to the class of germ cell tumors which are relatively rare intracranial tumors. Early recognition of this neoplasm is vital as germinomas are highly radiosensitive and effective/early radiation therapy can result in relatively favourable overall prognosis. In this article we describe a 19 years old man who presented with pituitary tumor in the suprasellar region for which transsphenoidal decompression and biopsy was done. The histopathological examination confirmed it to be germinoma and he underwent craniospinal radiotherapy.